Feeling Free and Having an Authentic Inner Compass as Important Aspects of the Need for Autonomy in Emerging Adults’ Interactions With Their Mothers - Assor, Avi; Cohen, Rinat; Ezra, Ohad; Yu, Shi (Frontiers in Psychology, 2021)
We examined the hypothesis that there are two kinds of specific experiences that contribute to the satisfaction of the general need for autonomy in emerging adults, as reflected in volitional, self-endorsed, actions. These experiences are: (1) feeling free, and (2) feeling that one has an authentic inner compass (AIC). This hypothesis was examined in a study of colleges students in Israel (n = 163, mean age = 21.33), and in China (n = 72, mean age = 23.67). Students in both countries completed measures assessing experiences of freedom and AIC validation during contacts with mothers, volitional contacts with mothers, and vitality during contacts with mothers. Confirmatory factor analyses and invariance analysis supported the validity of the measures, and their equivalence across cultures. In the Israeli sample, students also completed a measure assessing the extent to which the sense of AIC validated by mother is based on intrinsic rather than extrinsic aspirations and goals. As expected, across cultures, participants distinguished between experiences of (a) AIC validation and (b) feeling free. The findings also suggest that feeling free and feeling AIC validation during contacts with mothers are associated with volitional contacts and subsequent vitality during these contacts. Also as expected, AIC validation was associated with volitional contacts with mothers, and subsequent vitality - only when the AIC validated by mother was based on intrinsic aspirations. The results suggest that in assessing people’s sense of AIC, it is important to consider the content of the aspirations and values on which this sense is based. The findings are consistent with the view that the need for autonomy includes two distinct strivings: to feel free, and to have an AIC; both promoting a global experience of need autonomy satisfaction, as indicated by feelings of volitional and self-endorsed action.